Large-Scale Analysis of Defects in Atomically Thin Semiconductors using Hyperspectral Line Imaging - Lim, Seungjae; Kim, Tae Wan; Park, Taejoon; Heo, Yoon Seong; Yang, Seonguk; Seo, Hosung; Suh, Joonki; Lee, Jae Ung (Small, 2024)
Point defects play a crucial role in determining the properties of atomically thin semiconductors. This work demonstrates the controlled formation of different types of defects and their comprehensive optical characterization using hyperspectral line imaging (HSLI). Distinct optical responses are observed in monolayer semiconductors grown under different stoichiometries using metal-organic chemical vapor deposition. HSLI enables the simultaneous measurement of 400 spectra, allowing for statistical analysis of optical signatures at close to a centimeter scale. The study discovers that chalcogen-rich samples exhibit remarkable optical uniformity due to reduced precursor accumulation compared to the metal-rich case. The utilization of HSLI as a facile and reliable characterization tool pushes the boundaries of potential applications for atomically thin semiconductors in future devices.
Keywords: Atomically thin semiconductor; HyperSpectral; Large-scale analysis; Metal-organic chemical vapour depositions; Optical characterization; Optical response; Property; Simultaneous measurement; Thin semiconductor; Transition metal dichalcegenides; atomically thin semiconductors; defect; hyperspectral imaging; transition metal dichalcegenides